2021
DOI: 10.1007/s12094-021-02621-w
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly low STAT3 and STAT5 responses are associated with poor outcome and an inflammatory gene expression signature in pediatric acute myeloid leukemia

Abstract: The relapse rate for children with acute myeloid leukemia is nearly 40% despite aggressive chemotherapy and often stem cell transplant. We sought to understand how environment-induced signaling responses are associated with clinical response to treatment. We previously reported that patients whose AML cells showed low G-CSF-induced STAT3 activation had inferior event-free survival compared to patients with stronger STAT3 responses. Here, we expanded the paradigm to evaluate multiple signaling parameters induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…These findings indicate that STAT3β is pivotal for a G-CSF-induced myeloid differentiation program in AML blasts. As we did not observe alterations in G-CSF receptor ( Csf3r ) mRNA expression or in proliferation upon G-CSF stimulation, we assume that the absence of STAT3β does not affect receptor expression per se, but rather impairs endosomal recycling of the receptor causing reduced signaling, as previously suggested [ 46 48 ]. However, to obtain more detailed mechanistic insights further research is required.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings indicate that STAT3β is pivotal for a G-CSF-induced myeloid differentiation program in AML blasts. As we did not observe alterations in G-CSF receptor ( Csf3r ) mRNA expression or in proliferation upon G-CSF stimulation, we assume that the absence of STAT3β does not affect receptor expression per se, but rather impairs endosomal recycling of the receptor causing reduced signaling, as previously suggested [ 46 48 ]. However, to obtain more detailed mechanistic insights further research is required.…”
Section: Discussionsupporting
confidence: 70%
“…In vivo, we also identified a reduction in myeloid lineage commitment in blasts lacking STAT3β, together with more rapid disease progression. Consistent with this, pediatric AML patient samples with low STAT3 phosphorylation upon G-CSF stimulation showed poorer OS than patients with a stronger STAT3 response [ 46 ].…”
Section: Discussionmentioning
confidence: 60%
“…The STAT3/5 signaling pathway is induced in leukemic blasts by environmental factors such as granulocyte colony-stimulating factor stimulation or interactions with stromal cells. Narayanan et al showed that AML patients with low environment-induced STAT3 pathway signaling had inferior outcomes compared to patients with a stronger inducible STAT3 response [23].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of STAT3 is associated with shorter survival and poor clinical outcome in BMDSC, which is correlated with disease-initiating stem cells. 179 Inhibition of STAT3 by AZD9150, an antisense STAT3 inhibitor, decreased viability along with in vivo leukemic growth and induced LSCs' apoptosis. 180 Incorporation of AZD9150 with AML/MDS stem cells induced hematopoietic differentiation.…”
Section: Signaling Pathways Governing Lsc Maintenancementioning
confidence: 99%